Fat supplementation containing high palmitic acid enriched with lecithin on the performance, egg quality, and fatty acid profile of quail - Yano, A. A.; Hermana, W.; Retnani, Y.; Syarif, I. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
This study examined the effects of fat supplementation with high palmitic acid enriched with lecithin on the performance, egg quality, and fatty acid profile of quails. This study applied a completely randomized design to 330 female quails (Cortunix cortunix japonica) which were allocated into 5 different groups with 3 replicates of 22 birds. The groups were assigned as follows: T0 = commercial diet (control), T1 = commercial diet + 2.5% fat + 6% lecithin of added fat, T2 = commercial diet + 2.5% commercial fat, T3 = commercial diet + 5% fat + 6 % lecithin of added fat, T4 = commercial diet + 5% commercial fat. The results showed that the treatment group did not give effects on performances. However, the treatment group with fat level of 2.5% and 5% increased the score of egg yolk and eggshell thickness. Moreover, the treatment group decreased fat content in terms of saturated fatty acids and n-6/n-3 ratio of quail eggs. In conclusion, fat supplementation containing high palmitic acid enriched with lecithin proves effective in improving egg quality. However, the performance remains relatively similar across the groups.